Curcumin changes the polarity of tumor‐associated microglia and eliminates glioblastoma. Issue 12 (24th September 2016) - Mukherjee, Sumit; Baidoo, Juliet; Fried, Angela; Atwi, Doaa; Dolai, Sukanta; Boockvar, John; Symons, Marc; Ruggieri, Rosamaria; Raja, Krishnaswami; Banerjee, Probal
Abstract : Glioblastoma (GBM) is one of the most pernicious forms of cancer and currently chances of survival from this malady are extremely low. We have used the noninvasive strategy of intranasal (IN) delivery of a glioblastoma‐directed adduct of curcumin (CC), CC‐CD68Ab, into the brain of mouse GBM GL261‐implanted mice to study the effect of CC on tumor remission and on the phenotype of the tumor‐associated microglial cells (TAMs). The treatment caused tumor remission in 50% of GL261‐implanted GBM mice. A similar rescue rate was also achieved through intraperitoneal infusion of a lipid‐encapsulated formulation of CC, Curcumin Phytosome, into the GL261‐implanted GBM mice. Most strikingly, both forms of CC elicited a dramatic change in the tumor‐associated Iba1+ TAMs, suppressing the tumor‐promoting Arginase1 high, iNOS low M2‐type TAM population while inducing the Arginase1 low, iNOS high M1‐type tumoricidal microglia. Concomitantly, we observed a marked induction and activation of microglial NF‐kB and STAT1, which are known to function in coordination to cause induction of iNOS. Therefore, our novel findings indicate that appropriately delivered CC can directly kill GBM cells and also repolarize the TAMs to the tumoricidal M1 state. Abstract : What's new? Curcumin is widely known for its culinary uses, though it is also gaining recognition for its anticancer activity, demonstrated primarily in cells with limited success in vivo, due to low bioavailability. To overcome this obstacle, the authors of the present study coupled curcumin to a glioblastoma (GBM‐)‐specific antibody and administered it intranasally in mice. The treatment caused a dramatic switch in tumor‐associated microglia, with repolarization from a population of tumor‐promoting M2‐type cells to a milieu of tumoricidal M1‐type cells. Treatment also led to tumor remission in 50–60% of GBM‐harboring mice.